COMPARATIVE ANALYSIS THE ROLE OF ISLAMIC AND CONVENTIONAL MICROFINANCE INSTITUTIONS IN SUPPORTING THE WELFARE OF ECONOMICALLY VULNERABLE COMMUNITIES - Fakhri Muhammad Ario Putra; Alfin Husna Ridho Pangestu; Al-Anshari; Filzah Aulia (Journal of Management and Islamic Finance, 2024)
This study compares the performance of Conventional Microfinance Institutions (MFIs) and Sharia Microfinance Institutions (SMFIs) in supporting the welfare of economically vulnerable communities. The results show that SMFIs have an advantage in terms of social impact and financial inclusion for the poor, while MFIs excel in profitability and business expansion. However, both have different challenges in terms of liquidity stability and financial risk. This study recommends adaptive and inclusive policies, as well as optimizing the potential of social funds such as zakat, infaq, sadaqah, and waqf (ZISWAF) to support the sustainability of MFIs. Future research should further investigate the optimization of ZISWAF social funds in supporting the sustainability of microfinance institutions, analyze adaptive and inclusive policy models for both types of institutions, and evaluate strategies for improving liquidity stability and financial risk management.